Creating a context as the base for entrepreneurial support policy - Mandysová, Ivana (Univerzita Pardubice, 2012)
This study advances knowledge in the field of entrepreneurship policy and lays out a path for policymakers to follow. It highlights some of the major challenges faced by governments in evaluating the impact of policies and measures geared towards producing higher levels of entrepreneurial activity and discuss the potentially conflicting perspectives of entrepreneurs, policymakers and service providers. In this study we present the findings of entrepreneurship support policy stated in author´s monograph including theoretical background of entrepreneurship support policy and its policy foundations and entrepreneurship policy framework. We discuss conceptual issues related to steps identifying entrepreneurship policy measures; the appropriate choice of entrepreneurship support policy options and several issues concerning the improvements of entrepreneurship policies and programs. We introduce the Context model for Entrepreneurial Support that may be useful to government in taking stock of its current policy orientation and to better enable the assessment of entrepreneurship policy across country. We conclude with a discussion of how to approach the development of an integrated entrepreneurship policy approach and the future implications of this for policymakers, researchers, and economic development agents.
Keywords: entrepreneur; entrepreneurship; entrepreneurial support; entrepreneurship policy; policy measures